2017
DOI: 10.1116/1.4978553
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam assisted organic chemical vapor etch of magnetic thin films

Abstract: An ion beam-assisted organic vapor etch process is demonstrated for patterning magnetic metal elements for potential applications in magnetoresistive random access memory devices. A thermodynamic analysis was performed to evaluate the feasibility of a chemical etch process, leading to the selection of acetylacetone (acac) and hexafluoroacetylacetone (hfac) chemistries. First, etching of cobalt and iron in acac and hfac solutions was studied, and it was determined that acac etches Co preferentially over Fe with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…95) A highly etching selectivity of the metal oxide relative to the metal by organic vapor was achieved, suggesting that one of the most important requirements in atomic layer etching, a self-limiting reaction, was 3 nm=min). 94) satisfied. 96) By tuning the oxide thickness generated by O 2 plasma exposure, the etching of metals can be controlled at an atomic level.…”
Section: Atomic Layer Processing Of Multiferroic Materialsmentioning
confidence: 93%
See 2 more Smart Citations
“…95) A highly etching selectivity of the metal oxide relative to the metal by organic vapor was achieved, suggesting that one of the most important requirements in atomic layer etching, a self-limiting reaction, was 3 nm=min). 94) satisfied. 96) By tuning the oxide thickness generated by O 2 plasma exposure, the etching of metals can be controlled at an atomic level.…”
Section: Atomic Layer Processing Of Multiferroic Materialsmentioning
confidence: 93%
“…The volatility of the etching products was calculated to aid the selection of patterning chemistries, and this approach has been demonstrated successfully for test cases involving both halogen and organic etching chemistries. 93,94) One major consideration for enabling the ALEt of metallic and intermetallic thin films is the transformation of the metallic surface through physical or chemical means. Work on the use of Ar + in conjunction with acac chemistry has shown that ionic bombardment of cobalt thin films results in physical modification of the surface, generating additional active surface sites, disrupting the Co lattice by Ar bombardment, and allowing acac ligands to bond with Co to form Co(acac) 2 , using a cycle etching process.…”
Section: Atomic Layer Processing Of Multiferroic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to mitigate the detrimental effects of downstream deposition and prevent disastrous results of thermal run-away, it is necessary to gain a fundamental understanding of the chemical processes taking place and further determine how these processes respond to changes in processing conditions [8]. The methods of thermodynamic assessment have been demonstrated as useful tools in estimating the ranges for the desirable and undesirable reaction products [9]. Further kinetic and mechanistic studies of the deposition process are needed to gain insight into the dynamics of the run-away reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Наноразмерные структуры и пленки с различной шириной запрещенной зоны на основе Si могут применяться при создании различных структур типа металл−диэлектрик−полупроводник и полупроводник−диэлектрик−полупроводник, транзисторов и диодов сверхвысокой частоты, приборов солнечной энергетики и др. При создании таких структур наиболее перспективными являются кобальт и силициды кобальта [1][2][3][4]. В частности, для увеличения КПД солнечных элементов необходимо создавать структуры, которые интенсивно поглощают световое излучение в области энергий от 0.3-0.4 до 3.5−4 eV.…”
unclassified